Kolaborasi perguruan tinggi, gereja, dan masyarakat adat dalam advokasi isu lingkungan dan tenurial di Lembah Kebar Kabupaten Tambrauw: Collaboration of universities, spirituall organization and indigenous peoples in advocacy for environmental and tenure issues in Kebar Valley, Tambrauw Regency - Padang, Dina Arung; Runtuboi, Yubelince Y.; Nebore , Idola Dian Y.; Tampang, Ana; Sebayang, Sri Rosepda; Ayomi, Adomina; Mambraku , Selviana; Bauw, Naswa Anissa Az Zahra Sanusi; Fatem, Sepus M. (Fakultas Peternakan Universitas Papua, 2025)
ABSTRACT Natural resources, environmental sustainability, and tenure rights represent complex and persistent challenges faced by Indigenous communities across Indonesia, including in Kebar Valley, Tambrauw Regency, West Papua. This region has been under growing pressure from oil palm plantation expansion, leading to land conflicts, violence, and ecological degradation. This study explores the strategic collaboration among universities, churches, and Indigenous communities in advancing advocacy rooted in ecological justice and tenure recognition. A descriptive qualitative approach with a naturalistic paradigm and ethnographic methods was employed to uncover local narratives, social practices, and customary values that shape collective strategies in addressing structural inequalities. Data were collected through participatory observation, in-depth interviews, and documentation of advocacy activities. The findings reveal that such cross-sector collaboration has successfully mobilized socio-political strength to promote ulayat land rights, environmental preservation, and community-based economic resilience. The 2024 Declaration of Kebar Valley as the Land of the Gospel marks both a symbolic and strategic milestone, reinforcing solidarity among actors. This partnership has created momentum for progressive policy development, including both regulatory and non-regulatory frameworks at local and national levels. The study underscores the critical role of participatory approaches, recognition of Indigenous knowledge, and integration of spiritual values in empowering Indigenous peoples in resource governance. Future advocacy efforts must encompass sociocultural, economic, and legal dimensions to ensure the sustainability of Indigenous territories and the well-being of local communities. Keywords: Advocacy; Collaboration; Community; Kebar; Tambrauw ABSTRAK Isu sumber daya alam, lingkungan, dan hak tenurial merupakan permasalahan kompleks yang dihadapi masyarakat adat di Indonesia, termasuk di Lembah Kebar, Kabupaten Tambrauw, Papua Barat. Kawasan ini mengalami tekanan akibat ekspansi perkebunan kelapa sawit yang menimbulkan konflik lahan, kekerasan, dan degradasi ekologis. Penelitian ini mengkaji kolaborasi antara perguruan tinggi, gereja, dan masyarakat adat dalam upaya advokasi berbasis keadilan ekologis dan hak tenurial. Pendekatan kualitatif deskriptif dengan paradigma naturalistik dan metode etnografi digunakan untuk menggali narasi lokal, praktik sosial, dan nilai-nilai adat yang membentuk strategi kolektif komunitas dalam menghadapi ketimpangan struktural. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan dokumentasi aktivitas advokasi. Hasil penelitian menunjukkan bahwa kolaborasi lintas aktor ini mampu membangun kekuatan sosial-politik dalam mendorong pengakuan hak ulayat, pelestarian lingkungan, serta penguatan ekonomi komunitas. Deklarasi Lembah Kebar sebagai Tanah Injil (2024) menjadi tonggak simbolik sekaligus strategis dalam memperkuat solidaritas antar aktor. Kolaborasi tersebut membuka ruang bagi terobosan kebijakan baik dalam bentuk regulasi maupun non-regulasi di tingkat lokal dan nasional. Penelitian ini menegaskan pentingnya pendekatan partisipatif, pengakuan terhadap kearifan lokal, dan integrasi nilai spiritual dalam memperkuat posisi masyarakat adat dalam tata kelola sumber daya alam. Advokasi ke depan harus mencakup dimensi sosial-budaya, ekonomi, dan hukum untuk menjamin keberlanjutan ruang hidup dan kesejahteraan komunitas adat secara menyeluruh. Kata kunci: Advokasi; Kebar; Kolaborasi; Mayarakat; Tambrauw